Relevansi Sila Ketuhanan Yang Maha Esa Dengan Pengamalan Tauhidullah Bagi Masyarakat Muslim di Indonesia - Rohman, Abdul (Jurnal Keislaman, 2024)
This article discusses the relevance of the first principle of Pancasila for the realization of religious harmonization in Indonesia, which is still seen as contrary to the concept of tauhidullah for muslim communities in Indonesia. The author identifies these problems, including the relationship between the first principle or Pancasila and tauhidullah, the relationship between muslim and non muslim in national and state life, as well as the relevance of the principle og Belief in One Almighty God and tauhidullah fir muslim community in Indonesia . The result of the research include: (1) The relationship between the first principle of Pancasila and the concept of tauhidullah, namely that both attempt to teach the concept of the oneness of God; (2) The first principle of Pancasila and the concept of tauhidullah teach the importance of good relations between muslim and non muslim in the live of plural society in Indonesia; (3) The rinciples of belief in the Almightty God and the concept of tauhidullah have close relevance, especially maintaining tolerance between religious communities.